Issues in the Integration of Educational Technology into English Language Teaching Programme: An Empirical Study - Ali, Md Maksud (IIUC Studies, 2016)
Technology, as everybody will agree, is increasingly getting involved in language education. In teaching English as an International Language (EIL), as a matter of fact, there is an apparent need for integrating technology into English Language Teaching (ELT) education. This need has eventually brought about a new scope for ELT in the form of a new genre: Computer Assisted Language Learning (CALL). Following a Mixed Method Approach, this study investigates some of the issues relating to the use of CALL in the Department of English Language and Literature (ELL) at International Islamic University Chittagong (IIUC). The findings indicate some barriers that seem to impede the integration and the implementation of CALL in the department. IIUC Studies Vol.10 & 11 December 2014: 145-156